Britain, NATO and Nuclear Weapons - Booth, Ken. author. aut Link
XII, 374 p.
Keywords: An examination of nuclear arms control and defence containing papers that present opposing sides of the debate. Nuclear deterrence, Britain's defence budget, the state of Anglo-American relations, NATO strategies and Mr Gorbachev's security arrangements in Europe proposals are discussed.